The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.4103/ijccm.ijccm_375_17
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation of patients who leave against medical advice in a tertiary teaching care institute

Abstract: Context:Discharge against medical advice or leave against medical advice (DAMA or LAMA) is a global phenomenon. The magnitude of LAMA phenomenon has a wide geographical variation. LAMA reasons are an area of concern for all involved in health-care delivery system.Aims and Objectives:The study aimed to evaluate cases of LAMA retrospectively in a tertiary teaching care institute (1) to find the magnitude of LAMA cases (2) to evaluate demographic and patient characteristics of these cases.Subjects and Methods:We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The incidence of LAMA has been studied to be higher in developing countries like India where the healthcare system is an amalgamation of national public health system, alternative medicine practitioners and private hospitals 1,7 . Recent retrospective and prospective evaluation done on LAMA patients by our study group in tertiary care teaching hospitals of North India found the prevalence of LAMA to be 3.3% from the hospital 3 , 2.4% from the emergency and 15% from the intensive care units (ICUs) 8 . In another survey conducted in a private Indian setup, 3.8% of the patients who presented to the emergency department left against medical advice 7 .…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The incidence of LAMA has been studied to be higher in developing countries like India where the healthcare system is an amalgamation of national public health system, alternative medicine practitioners and private hospitals 1,7 . Recent retrospective and prospective evaluation done on LAMA patients by our study group in tertiary care teaching hospitals of North India found the prevalence of LAMA to be 3.3% from the hospital 3 , 2.4% from the emergency and 15% from the intensive care units (ICUs) 8 . In another survey conducted in a private Indian setup, 3.8% of the patients who presented to the emergency department left against medical advice 7 .…”
Section: Discussionmentioning
confidence: 80%
“…The patient's withdrawal of treatment before the recommendation of discharge by the treating physician is diversely abbreviated as LAMA (leaving against medical advice), DAMA (discharge against medical advice), SAMA (signing against medical advice) 1 . It is a worldwide phenomenon in the healthcare system 2,3 . The prevalence rate of LAMA in literature varies from 0.002% 4 to around 43% 5 in different regions and patient populations around the world.…”
Section: Introductionmentioning
confidence: 99%
“…This is comparable with the study done in North India where they found the prevalence rate of LAMA from ICU was 15% while other study found 28.8% of the patients admitted in ICU were discharged on LAMA. 7,17 Our study had 62.60% male and 37.39% female among total LAMA patients. Both the medical and surgical patients were included in the study, and the patients leaving against medical advice from the medical ICU outnumbered those from the surgical ICU.…”
Section: Discussionmentioning
confidence: 83%
“…The reason for LAMA can be multifactorial, commonly divided as patient-related factors and hospital-related factors. In a study done by Gautam N et al 17 the authors describe the other less discussed and less studied reason for LAMA, as doctors promoting the patients to get discharged on LAMA, to avoid any unwanted legal issues that may arise during the course of treatment or regarding the possible outcome of the patient. However, Patrick J. Devitt has examined whether discharging patients against medical advice protects physicians from malpractice charges, and came to the conclusion that good clinical practice and thorough documentation should be maintained which serves as the best legal protection.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,10e12 The practice of leaving AMA varies across clinical departments, with high rates occurring among patients admitted to the intensive care units, and emergency department and low rates among obstetric patients. 4,10,13,14 Unlike patients of other clinical specialties, trauma patients typically present to acute care centers from accidental and unexpected acute injury. 3 Additionally, trauma patients are unlikely to make choices on the hospital, type of specialist, or type of procedure they need in acute events or emergencies.…”
Section: Introductionmentioning
confidence: 99%